DISTINCTIVE FEATURES OF COMPLEX OBJECTS: THEIR LEGAL AND PHILOSOPHICAL ESSENCE - Tukhtaev Uktamjon; Kubaeva Ismigul Farkhid kizi (PT. Antis International Publisher, 2025)
Objective: The objective of this article is to analyze the concept of complex objects from the perspectives of civil law and philosophy. It aims to deepen the study of the theory of objects in civil law, improve the legal system, and develop new approaches for defining complex objects in national legislation, particularly in Uzbekistan. Method: The study examines the distinctive features of complex objects, such as the absence of will, discreteness, and materiality, through an analysis of legal and philosophical perspectives. It also explores the interconnectedness of complex objects with other objects of civil law. Additionally, the research uses the experience of foreign countries to assess the possibilities of regulating complex objects within Uzbekistan’s civil legislation. Result: The research identifies the common characteristics of complex objects and their distinct features, providing a comprehensive understanding of how these objects relate to other civil law objects. It also highlights the potential for integrating these insights into Uzbekistan's legal system to improve the regulation of complex objects. Novelty: The novelty of this article lies in its interdisciplinary approach to the concept of complex objects, combining legal analysis with philosophical perspectives. The study also introduces the idea of applying foreign experiences to improve the regulation of complex objects in Uzbekistan’s civil law, offering a new approach to defining and understanding complex objects in national legislation.